(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
This review examines the cardioprotective properties of various traditional medicinal plants, highlighting their potential in treating and preventing cardiovascular diseases. The cardiovascular system’s complexity and the growing burden of heart diseases have led to increased interest in natural therapeutic alternatives. We analyze twelve significant medicinal plants: Shatavari (Asparagus racemosus), Amla (Phyllanthus emblica), Grapes (Vitis vinifera), Arjun Tree (Terminalia arjuna), Tulsi (Ocimum sanctum), Katuka (Picrorhiza kurroa), Indian Laburnum (Cassia fistula), Kokum (Garcinia indica), Fenugreek (Trigonella foenum-graecum), Fox Glove (Digitalis purpurea), Garlic (Allium sativum), and Turmeric (Curcuma longa). Each plant is evaluated for its phytochemical composition, traditional uses, and experimental evidence supporting cardioprotective effects. The review particularly focuses on their roles in preventing and treating various cardiac conditions, including myocardial infarction, hypertension, and other cardiovascular disorders. The experimental studies cited demonstrate these plants’ efficacy through various mechanisms, including antioxidant, anti-inflammatory, and direct cardioprotective actions. This comprehensive analysis provides a foundation for future research in developing natural cardioprotective therapeutics while acknowledging the traditional wisdom of various medical systems.